DEVELOPMENT AND EFFECTIVENESS OF SITUATIONAL APPROACH-BASED TEACHING MATERIALS FOR ARABIC SPEAKING SKILLS - Zuhri, Achmad Syaifuddin; Huda, Miftahul; Chamidah, Dewi; Bakhiet Ahmad, Bakri Muhammad (Institut Pendidikan Tapanuli Selatan, 2025)
Developing teaching materials is a crucial endeavor that contributes significantly to the success of teaching and learning activities. However, the materials in the Mamba'ul Ulum Senior High School handbook for learning students' speaking skills in Bungah, Gresik, are limited and do not allow students to practice speaking in different situations. The book only presents dialogue texts and scattered vocabulary. This makes it difficult for students to develop speaking skills. This research project aims to develop, produce, and evaluate teaching materials that enhance students' speaking skills in response to daily situations. This study employs a qualitative and quantitative approach with a research and development (R&D) method. The results of this study are as follows: (1) Teaching materials were developed for Arabic language students at Mamba'ul Ulum Senior High School in Bungah, Gresik, through a process involving needs analysis, planning, material development, expert validation, improvement, field trials, and final revisions. (2) The use of teaching material products that have been designed through the development process is very effective in improving students' speaking skills. This is evidenced by post-test results that are higher than pre-test results. This study suggests the following: First, teachers should design teaching materials that align with students' needs and interests related to their daily lives. Second, teachers should use a variety of methods and strategies, and they should avoid using the students' native language. Researchers have designed speaking skills teaching materials that can support Arabic-speaking instruction at Mamba'ul Ulum High School in Bungah, Gresik, and other educational institutions.